Watuchicuna (Adivinanzas quechuas) - Altamirano, Teófilo (1984)
Riddles represent a form of competition in the Andes, they constitute social and recreational events; They include varied content, and are often satires of everything external to the community. They reveal the peasant's knowledge of his world. Here the author offers us a sample of these riddles, in Quechua, collected in the regions of Apurímac, Ayacucho, and in Lima, by himself.